PROGRAM PENANGANAN GELANDANGAN DAN PENGEMIS DI KABUPATEN JEMBER (HANDLING PROGRAMS OF HOMELESS AND BEGGAR) IN JEMBER DISTRICT) - Nusanto, Baktiawan (Universitas Muhammadiyah Jember, 2017)
number of homeless and beggars in Jember District tend to increase from year to year. In addition to the lack of social service in the implementation of homeless and begging programs, the increasing number of homeless and beggars is also caused by the increasing number of poverty in Jember regency. Until 2015 the number of homeless and beggars in Jember Regency reached 801 people.In the effort to handle the problem of homeless and beggars, the Jember District Social Service has implemented various programs including: (1) Social education in homeless place and beggars are located; (2) Family empowerment, basic needs fulfillment, health and education services, employment and family income; (3) Establish postal service posts and beggars to provide consultation, data collection, networking, referrals for homeless and beggars to be followed up by the rehabilitation process; (4) Conducting Raids in places where homeless and beggars are often located. The raids were conducted after social counseling was initiated to recruit homeless and beggars who were temporarily housed in a shelter barracks before being sent to social rehabilitation centers; (5) Optimizing UPTD functions Liposos and NGOs dealing with homeless and beggars; (6) Cooperation with the business world in order to employ the homeless and beggars.Keywords: Handling Program, Homeless and Beggar